Aging and erectile function. (9th April 2021) - Meldrum, David R.; Morris, Marge A.; Gambone, Joseph C.; Esposito, Katherine
Abstract: The authors review and discuss numerous factors that influence erectile function and their interactions, based on the published literature. Of critical importance are vascular nitric oxide; nutrition; exercise; weight control and maintaining insulin sensitivity; early treatment of hypertension with attention to effects on erectile function; avoiding sources of oxidative stress such as obesity and smoking; reducing inflammation (e.g. from gingivitis); improving pelvic floor muscle strength; and inhibiting cyclic GMP break-down. The described interventions act on different aspects of erectile biochemistry and physiology. Therefore, combining multiple therapeutic approaches will yield maximum benefits for erectile and vascular and general health.